2022
DOI: 10.1021/acs.jafc.2c02603
|View full text |Cite
|
Sign up to set email alerts
|

Digestion Resistance of Soybean 7S Protein and Its Implications for Reinforcing the Gastric Mucus Barrier

Abstract: Previous studies have found that soybean protein, especially soybean 7S protein (β-conglycinin), exhibits digestion resistance, but the mechanism of digestion resistance and its implications for human health are still unclear. Here, we show that the extracted soybean 7S protein contains both oligomer globulins and amyloid aggregates, while the gastric digested soybean 7S protein only contains amyloid aggregates and thus exhibits digestion resistance. An animal experiment shows that un-digestible soybean 7S pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
(110 reference statements)
2
16
0
Order By: Relevance
“…To visualize the unfolding of protein amyloid aggregates by model bile, the fluorescence probe ThT was used to detect the cross-β sheet structure in amyloid aggregates or fibrils Figure b shows CLSM images of the ThT-stained gastric digests of soybean 7S protein and found that ThT binds to protein with high fluorescence intensity (green dots), confirming the structural characteristics of amyloid aggregates . Upon increasing the concentration of model bile, the overall trend of decreased ThT fluorescence intensity is observed, showing the unfolding capacity to protein amyloid aggregates by physiologically relevant colloidal structures containing both dihydroxy and trihydroxy BS (Figure c).…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…To visualize the unfolding of protein amyloid aggregates by model bile, the fluorescence probe ThT was used to detect the cross-β sheet structure in amyloid aggregates or fibrils Figure b shows CLSM images of the ThT-stained gastric digests of soybean 7S protein and found that ThT binds to protein with high fluorescence intensity (green dots), confirming the structural characteristics of amyloid aggregates . Upon increasing the concentration of model bile, the overall trend of decreased ThT fluorescence intensity is observed, showing the unfolding capacity to protein amyloid aggregates by physiologically relevant colloidal structures containing both dihydroxy and trihydroxy BS (Figure c).…”
Section: Resultsmentioning
confidence: 87%
“…3 More recently, we have elucidated that the indigestible intact protein (50 kDa) is the innate amyloid aggregates of 7S protein, and gastric digestion further triggers the novel formation of amyloid aggregates. 10 In this study, we isolated undigested protein aggregates from pepsin-trypsin digests of different soybean proteins (SPI, 11S, and 7S) by ultracentrifugation and analyzed in parallel by native-PAGE and SDS-PAGE. As shown in Figure 2a,b, the undigested fractions of SPI and 7S protein are composed of residue 7S protein amyloid aggregates and peptide fragments, while 11S and heated 7S protein (boiling for 30 min) only contain peptides fragments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations